Ландшафти рівнинного району дендропарку “Тростянець” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Changes in a composition of landscapes, number and species structure of wood plantings of a site typical for flat area which have occurred during last 50 years are analyzed. Ways of restoration of the disturbed compositions are planned.